PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP PAJAK PENGHASILAN PADA PT. SEMEN INDONESIA (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - CORRINA, FATTI; MELLIOFATRIA, MELLIOFATRIA (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
The purpose of this study was to examine whether capital structure and profitability have an effect on corporate income tax partially and simultaneously. This research is included in quantitative research. This research was conducted from 2012 – 2021. Sampling using purposive sampling technique. The statistical method used is multiple linear regression analysis using SPSS version 26 to process the data. The analytical methods used include descriptive statistical tests, classic assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, determination tests and hypothesis testing. Based on the results of the research and discussion, several conclusions can be drawn as follows: Capital structure and profitability simultaneously have a significant effect on the income tax variable at PT. Semen Indonesia (Persero) Tbk on the Indonesia Stock Exchange. Partial capital structure has no significant effect on income tax variables at PT. Semen Indonesia (Persero) Tbk on the Indonesia Stock Exchange. Profitability partially has no significant effect on income tax variables at PT. Semen Indonesia (Persero) Tbk on the Indonesia Stock Exchange. Operational costs partially have a significant effect on income tax variables at PT. Semen Indonesia (Persero) Tbk on the Indonesia Stock Exchange